In Vitro Fertilization in Mice Using the MBCD‐GSH Protocol. Issue 2 (16th June 2014) - Guan, Mo; Bogani, Debora; Marschall, Susan; Raspa, Marcello; Takeo, Toru; Nakagata, Naomi; Fray, Martin
Abstract: Historically, timed mating of either naturally cycling or superovulated females has been the mainstay of pre‐implantation embryo production. However, rising cage costs and the rapid expansion of biomedical research programs has necessitated the development of high‐throughput approaches to mouse embryo production. In vitro fertilization (IVF) represents one such versatile tool offering many advantages to busy mouse facilities in terms of efficient use of space and resources. For example, strains can be taken off the shelf, frozen quickly as sperm, and recovered at a later date, small colonies can be rapidly expanded to meet demand, and IVF can be used to rescue strains that fail to breed or where the founder male is ill or has died suddenly. This article describes an IVF protocol currently used by many reproductive technologists to assist mouse biology programs. Curr. Protoc. Mouse Biol . 4:67‐83 © 2014 by John Wiley & Sons, Inc.